2020
DOI: 10.1111/jfpp.15073
|View full text |Cite
|
Sign up to set email alerts
|

Application of composite cassava starch/chitosan edible coating to extend the shelf life of black mulberries

Abstract: Black mulberry (Morus nigra) is a highly valuable commodity because of its nutritional properties and flavor. However, dehydration and microbial spoilage affect its quality during refrigerated storage. The objectives of this work were to select and apply a composite edible coating to minimize weight losses and microbial spoilage of black mulberries. Optimization indicated that a composite edible coating of chitosan and cassava starch (1:1) was effective for minimizing weight loss and mold decay. This edible co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It has also been observed that in CS-coated plums a lower increase of anthocyanin content during storage ascribable to the suppression of respiratory activity that allows to slow down the anthocyanin’s synthesis with the decrease in the enzymes activity such as PAL and anthocyanidin synthase (ANS) associated with postharvest ripening [ 56 ]. Contrarily, in other studies have been observed that CS-based coatings improved the anthocyanin content of strawberry, black mulberry, loquat, fig, sweet cherry, pomegranate, and pomegranate arils [ 11 , 45 , 47 , 90 , 94 , 108 , 115 ] suggesting that CS delays fruit senescence and enhances the phytochemicals content during storage. An opposite trend was found by Zam [ 106 ] which report that the dense structure of CS-based coating enriched with olive leaves extract reduced the increase of anthocyanins, probably due to changes in the fruit internal atmosphere during storage compared to uncoated fruits.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 85%
See 2 more Smart Citations
“…It has also been observed that in CS-coated plums a lower increase of anthocyanin content during storage ascribable to the suppression of respiratory activity that allows to slow down the anthocyanin’s synthesis with the decrease in the enzymes activity such as PAL and anthocyanidin synthase (ANS) associated with postharvest ripening [ 56 ]. Contrarily, in other studies have been observed that CS-based coatings improved the anthocyanin content of strawberry, black mulberry, loquat, fig, sweet cherry, pomegranate, and pomegranate arils [ 11 , 45 , 47 , 90 , 94 , 108 , 115 ] suggesting that CS delays fruit senescence and enhances the phytochemicals content during storage. An opposite trend was found by Zam [ 106 ] which report that the dense structure of CS-based coating enriched with olive leaves extract reduced the increase of anthocyanins, probably due to changes in the fruit internal atmosphere during storage compared to uncoated fruits.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 85%
“…It has been also reported that, the addendum of olive leaves, pomegranate peel, apple peel, stevia extract and cassava starch into CS coating reduced the gradual decline in TP and/or TF in strawberry [ 47 ], guava [ 82 ], litchi [ 105 ], sweet cherry [ 106 ], fresh-cut apple [ 107 ], and black mulberry [ 108 ] during storage. Furthermore, nanostructured CS/propolis coated strawberry fruits exhibited the highest TP content on each day of cold storage [ 109 ].…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21,24,26 ] Another disadvantage of this method is related to the possibility of the coating solution diluting other layers of the food surface and degrade its functionality. [ 31 ] This technique has been widely used, mainly for coating of fresh products as Andean blueberries, [ 25 ] eggplants, [ 32 ] cucumbers, [ 33 ] mangoes, [ 34 ] black mulberries, [ 35 ] pomegranate fruit, [ 36 ] mandarins, [ 37 ] and pumpkins, [ 38 ] and to recover and protect chestnuts [ 39 ] and almonds. [ 40 ]…”
Section: Production and Application Of Starch‐based Coatingsmentioning
confidence: 99%
“…[21,24,26] Another disadvantage of this method is related to the possibility of the coating solution diluting other layers of the food surface and degrade its functionality. [31] This technique has been widely used, mainly for coating of fresh products as Andean blueberries, [25] eggplants, [32] cucumbers, [33] mangoes, [34] black mulberries, [35] pomegranate fruit, [36] mandarins, [37] and pumpkins, [38] and to recover and protect chestnuts [39] and almonds. [40] The spraying technique is one of the most used processes of coating materials deposition due to the wide possibility of macromolecules used and the great versatility regarding irregular shapes and different sizes (Figure 1d).…”
Section: Production and Application Of Starch-based Coatingsmentioning
confidence: 99%